Upaya Meningktakan Hasil Belajar Matematika Menggunakan Model Pembelajaran Problem Based Learning (PBL) Peserta Didik Kelas IV SDN 13 Mataram Tahun Pelajaran 2022/2023 - Rahmaputri, Olliviani; Yuniani, Ni Kadek Dwi; Rohyani, Helmi; Arjudin, Arjudin (Journal of Science Instruction and Technology, 2023)
This classroom action research aims to improve student learning outcomes in Mathematics lessons using the Problem Based Learning (PBL) learning model for class IV students at SDN 13 Mataram. This type of research is classroom action research (PTK) while the approach used is a descriptive quantitative approach. This research was carried out at SDN 13 Mataram. The subjects of this research were class IV students consisting of 26 students. The object of this research is the learning outcomes of students. This research was carried out in three cycles which were carried out collaboratively between researchers and tutor teachers. The data collection techniques used were tests and observation sheets. The results of this research show that the use of the Problem Based Learning (PBL) learning model in learning can improve the learning outcomes of class IV students at SDN 13 Mataram. This increase is shown in the quality of the learning process, activeness, enthusiasm and student learning outcomes. The increase in student learning outcomes can be seen from the average value of student learning outcomes from pre-cycle to cycle II. In the pre-cycle the average student score was 68, increased in cycle I to 74, then experienced another increase in cycle II of 81. The percentage of completion from cycle I and cycle II was 60% (16 students) respectively, increasing in cycle II to 80% (21 students). Because it has reached the criteria for completion, namely 80% of students obtained more marks or up to the KKM (75), this research is said to have been successful in two cycles.